POLIGAMI: ANTARA LEGALITAS FORMAL DAN LEGALITAS BUDAYA (Studi Kasus Praktek Poligami Kyai Pesantren di Probolinggo Jawa Timur) - Musarrofa, Ita (Islamic University of Indonesia, 2005)
Law is not only as a tool of social control but also as that of social engineering. As a tool of social engineering, law can be conducted to direct and change society, so did the restrictive decision regarding poligamy of Act No. 1 year 1974. The goal of this act is to direct and to regulate poligamy to become responsible and regularly. The main problem in this context is is it possible the restrictive can be conducted by society effectively while the phenomemon of poligamy tends to contrary to this act? The result of this researh revealed that the restrictive decision of poligamy of this act in term of the effectivity, the community of kiyai of pesantren at Probolinggo East Java, this act did not run effectively. This means that is not in accordance with the act. This happens because of internal motivation of kiyai factor and external or culture as supported factor.